2020
DOI: 10.3390/admsci10010005
|View full text |Cite
|
Sign up to set email alerts
|

Drivers toward Social Entrepreneurs Engagement in Poland: An Institutional Approach

Abstract: The aim of this study is to identify the factors that influence the involvement of individuals in social entrepreneurship in Poland from an institutional economics perspective. The research is based on exploratory data analysis using qualitative data covering 22 interviews with social entrepreneurs and 10 representatives of stakeholders from Poland as well as observations and secondary data. By employing an inductive approach and a case study methodology, it can be stated that involvement of social entrepreneu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 66 publications
(69 reference statements)
3
30
0
1
Order By: Relevance
“…Qualitative research what have elaborated in his research, "Drivers toward Social Entrepreneurs Engagement in Poland: An Institutional Approach" [11] qualitative methods allow for a thorough understanding of entrepreneurial activities and their context; cultural or social as well as their relationships with the immediate environment. Meanwhile the selection of representatives of social enterprises to be interviewed as part of the collective case study was based on the principle of theoretical replication.…”
Section: Methodsmentioning
confidence: 99%
“…Qualitative research what have elaborated in his research, "Drivers toward Social Entrepreneurs Engagement in Poland: An Institutional Approach" [11] qualitative methods allow for a thorough understanding of entrepreneurial activities and their context; cultural or social as well as their relationships with the immediate environment. Meanwhile the selection of representatives of social enterprises to be interviewed as part of the collective case study was based on the principle of theoretical replication.…”
Section: Methodsmentioning
confidence: 99%
“…Also, Brinckerhoff (2000) argues that reducing bureaucracy and eliminating unnecessary regulations are important factors that stimulate the sustainable development of SEs. The government's challenges concern not only the bureaucracy in obtaining public funds, but also a number of other regulations that limit the development opportunities of SEs in the social economy ecosystem (Pacut, 2020). These include, for example, the regulation of the legal form of a social enterprise.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Apart from the literature that explicitly addresses institutional entrepreneurship, another body of literature can be identified that deals with both institutions and entrepreneurship but does not explicitly refer to institutional entrepreneurship theory. Especially, this research stream not directly related to institutional entrepreneurship examines the favoring or inhibiting effects of existing institutions on entrepreneurial behavior (Bouncken et al 2020;Pacut 2020;Sobel 2008;Wang et al 2019;Welter and Smallbone 2011) and, more generally, on the emergence, flourishing, and success of entrepreneurship (Acs et al 2018;Aidis et al 2008;Ali et al 2020;Bouncken et al, 2020;Bowen and Clercq 2008;Dai and Si 2018;Eijdenberg et al 2019;Estrada-Robles et al 2018;Estrin et al 2013;Lv et al 2020;Galindo-Martín et al 2019;Manolova et al 2008;Queirós et al 2019;Urbano et al 2020), especially where institutional voids exist (Puffer et al 2010). Rather than institutional entrepreneurship's focus on institutional change, this body of research sees entrepreneurs as embedded in existing institutions.…”
Section: Performance Analysesmentioning
confidence: 99%
“…However, not only for-profit ventures are subject to institutional entrepreneurship but also social, cultural, and environmental ones. Therefore, an intersection of institutional entrepreneurship and social entrepreneurship can be seen in the literature (Dacin et al 2010(Dacin et al , 2011Pacut 2020).…”
Section: Introductionmentioning
confidence: 99%